Archeozoological study of the macromammal remains stratigraphically associated with the Magdalenian human burial in El Mirón Cave (Cantabria, Spain). (August 2015) - Marín-Arroyo, Ana B.; Geiling, Jeanne Marie
Abstract: The presence of abundant macromammal remains in the level in which the first Magdalenian human burial ever found in the Iberian Peninsula affords an outstanding opportunity to reconstruct aspects of the subsistence strategy of the hunter–gatherer group to which the deceased woman may have belonged. The analyses reported here, in addition to rejecting the hypothesis of deliberate faunal grave goods or funerary offerings, give us a better understanding of how Lower Magdalenian societies exploited available food resources, providing a first glimpse of how the El Mirón site fitted within the overall paleoeconomic framework of the Oldest Dryas phase of the Late Glacial in Cantabrian Spain. Furthermore, the particular location of the site at the ecotone between the Cantabrian Mountains and the valley of the Asón River, not far from the coastal lowlands, provides evidence of a highly efficient, productive system for exploiting the available ungulate game of the region. Highlights: Macromammal bones and teeth are found in El Mirón Magdalenian burial area. Faunal grave goods are not clearly identified. Lower Magdalenian paleoeconomic behavior is reconstructed.